2020
DOI: 10.1155/2020/6958246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ginkgo biloba on Early Decompression after Spinal Cord Injury

Abstract: Spinal cord injury (SCI) is a severe trauma of the central nervous system characterized by high disability and high mortality. Clinical progress has been achieved in understanding the pathological mechanism of SCI and its early treatment, but the results are unsatisfactory. In China, increasing attention has been paid to the role of traditional Chinese medicine in the treatment of SCI. In particular, extracts from the leaves of Ginkgo biloba (maidenhair tree), which have been reported to exert anti-inflammator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…The occurrence of SCIRI is di cult to avoid in many cases, and once it occurs, the prognosis is poor and the quality of life of patients is greatly affected, so the treatment after the occurrence is a challenge. GBE has the antioxidant effect of inhibiting ferroptosis, and it has been proved by experiments that GBE can promote the recovery of nerve function in rats with SCI 14 . However, the relationship between GBE and ferroptosis during SCIRI remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of SCIRI is di cult to avoid in many cases, and once it occurs, the prognosis is poor and the quality of life of patients is greatly affected, so the treatment after the occurrence is a challenge. GBE has the antioxidant effect of inhibiting ferroptosis, and it has been proved by experiments that GBE can promote the recovery of nerve function in rats with SCI 14 . However, the relationship between GBE and ferroptosis during SCIRI remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, due to the emergence of ferroptosis, a new form of cell death, some scholars interested in ferroptosis have con rmed that GB can inhibit ferroptosis 13 . As early as 2020, Guo et al 's research results showed that GB can further reduce the in ammatory response after decompression of spinal cord injury, and play a role in protecting neurons and repairing spinal cord injury 14 . However, the exact mechanism of action of GBE in the treatment of SCIRI remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Gingko Biloba has been demonstrated to attenuate mechanical and cold allodynia in a rat model of neuropathic pain, suggesting its use in managing neuropathic pain in humans [24]. In addition, other studies explored the effects of Gingko biloba on spinal cord neuron deterioration in several studies in vivo [25,26]. Finally, it is known to have effects on neuronal plasticity [27], leading to neuroprotection through anti-apoptotic activity [28] that, combined with its antioxidant effect [29,30], improved nerve repair.…”
Section: Introductionmentioning
confidence: 99%